2021
DOI: 10.3389/fphar.2020.626375
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Qishen Yiqi Dripping Pill for Heart Failure With Preserved Ejection Fraction: A Systematic Review and Meta-Analysis

Abstract: Background: The number of heart failure with preserved ejection fraction (HFpEF) patients is increasing year by year, yet all western medicines currently used for heart failure have been shown to be ineffective for HFpEF. Qishen Yiqi Dripping Pill is one of the commonly drugs for the treatment of heart failure in China. In recent years, some clinical studies found that it has curative effect on HFpEF.Objective: To evaluate the efficacy and safety of Qishen Yiqi Dripping Pill in treatment of HFpEF.Methods: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…There have been several systematic quantitative evaluation studies of CTPMs for the treatment of HFPEF, and these CTPMs are approved by the NMPA of China. Wang et al ( 9 ) conducted a systematic review that demonstrated the improvement in NYHA efficiency, E/A, 6MWT, and the reduction in BNP when using QSYQDP + CWM compared to CWM alone. Cao et al ( 11 ) and Ge et al ( 87 ) found that QLQXC + CWM improved clinical efficiency, E/A, 6MWT and reduced BNP, NT-proBNP and Minnesota living with heart failure questionnaire scores compared to CWM.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several systematic quantitative evaluation studies of CTPMs for the treatment of HFPEF, and these CTPMs are approved by the NMPA of China. Wang et al ( 9 ) conducted a systematic review that demonstrated the improvement in NYHA efficiency, E/A, 6MWT, and the reduction in BNP when using QSYQDP + CWM compared to CWM alone. Cao et al ( 11 ) and Ge et al ( 87 ) found that QLQXC + CWM improved clinical efficiency, E/A, 6MWT and reduced BNP, NT-proBNP and Minnesota living with heart failure questionnaire scores compared to CWM.…”
Section: Discussionmentioning
confidence: 99%
“…TDI measurements including systolic velocity (s’), early (e’), and late (a’) diastolic velocities were recorded at the septal mitral annulus in apical 4-chamber view ( 13 ). The transmitral to mitral annular early diastolic velocity ratio (E/e’) was calculated ( 14 , 15 ). We also defined the ratio of early and late diastolic velocities as the e’/a’ ratio ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta‐analysis showed that, compared to WM alone, a combination of WM and Qishen Yiqi dripping pills can further increase early to late diastolic transmitral flow velocity (E/A) (mean difference = 0.20, p < 0.00001), decrease early diastolic transmitral flow velocity to early diastolic mitral annular tissue velocity (E/e') (mean difference = −2.50, p < 0.00001), as well as ameliorate BNP levels and 6MWT distance ( p < 0.005). Nonetheless, additional well‐designed, large‐scale clinical studies are required to confirm these findings [39]. Several other RCTs have indicated that Qishen Yiqi dripping pills can ameliorate inflammation and ventricular remodeling [40, 41], as well as contribute to reducing fasting blood glucose and glycated hemoglobin (HbA1c) levels in HF patients with diabetes mellitus [42].…”
Section: Treatment For Hf By Itcwmmentioning
confidence: 99%